Evaluación financiera y su incidencia en la rentabilidad de la empresa comercializadora de neumáticos “Oña” cantón Valencia, período 2012-2013. - Villamar Quimiz, Derly Zimena (2015)
This research was conducted at the Distributor tire "Ona" which is located in the canton Valencia Los Rios province. The same is located 20 minutes from the city of Quevedo is located at coordinates 0 ° 57'09 '' south latitude and 79 ° 21'11 '' W, second largest, with 987.00 km2. The investigation lasted 210 days, the goal was to "assess the financial management and its impact on the profitability of the company marketing tires" Ona "Canton valencia, 2012-2013". He went to the premises of the marketing company of tires "Ona" Canton Valencia, for the collection of information through a questionnaire and financial statements based on the systematization of the problem and that the accountant and office staff applied the enterprise; also was used in the theoretical framework citations concerning financial evaluation, which allowed me to address the existing problems in the marketing company Ona. This type of research for the review of data or documents contained in written texts of scientific, technological networks (LAN), which will support or base for the development of research was used.Deduce properties or relations starting from the particular to the general. It will be used in the analysis of data logically, according to the results obtained from field research during the execution of the financial evaluation. According to the results the company has in its current assets of $ 1.62 for 2012 and 0.87 for 2013, noting a decrease from the previous year, means that the percentage of cost of sales is 94.91% in 2012 and 78.28% in 2013 compared to net sales of the company Ona, also within the leverage indicates that for every dollar of equity of the company Ona, Owe the 178% 166% 2012 and 2013, acceptable financial situation and that is within normal parameters.